2003
DOI: 10.17221/5764-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of canine coronavirus and parvovirus infections in dogs with gastroenteritis in Thailand

Abstract: Canine coronavirus (CCV) and canine parvovirus type 2 (CPV-2) are the causative agents of gastroenteritis in dogs. Seventy fecal samples from dogs with signs of gastroenteritis (vomiting and diarrhea), twenty-five fecal samples from healthy dogs and one CPV-2 vaccine strain were amplified by semi-nested polymerase chain reaction (PCR) and semi-nested reverse transcriptase polymerase chain reaction (RT-PCR), aimed at specifically studying the gene encoding the most abundant capsid protein VP2 of CPV-2 and spike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
3
10
0
1
Order By: Relevance
“…This study also showed that CPV‐2 was predominantly detected in dogs of young age (<1 year). These results were similar to the previous report of CPV‐2 in puppies in Thailand (Sakulwira, Vanapongtipagorn, Theamboonlers, Oraveerakul, & Poovorawan, ). It is important to note that CPV‐2c could also be isolated from cats.…”
Section: Discussionsupporting
confidence: 92%
“…This study also showed that CPV‐2 was predominantly detected in dogs of young age (<1 year). These results were similar to the previous report of CPV‐2 in puppies in Thailand (Sakulwira, Vanapongtipagorn, Theamboonlers, Oraveerakul, & Poovorawan, ). It is important to note that CPV‐2c could also be isolated from cats.…”
Section: Discussionsupporting
confidence: 92%
“…6 Viral and parasitic infections are very common in young puppies and are involved in weanling diarrhea. 5,6,14,[41][42][43] The early detection of such infections would avoid growth retardation and could decrease the development of more severe forms of the disease. Thus, noninvasive markers of digestive health, the concentrations of which might be modified by the presence of enteropathogens, would be of great utility in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of these viruses (Rimmelzwaan et al, 1991;Tennant et al, 1993;Bandai et al, 1999;Naylor et al, 2001b;Schulz et al, 2008). Moreover a higher prevalence of CCV and CPV2 was described in young animals under 6 months of age compared to adult dogs (Sakulwira et al, 2003;Gates and Nolan, 2009a,b;Epe et al, 2010). In addition to the wide distribution and contagiosity of these viruses, the methods used for detection of these viruses can also contribute to this high prevalence.…”
Section: Discussionmentioning
confidence: 99%